Environmental protection in administrative procedure - Vlajnić Jelena (Trendovi u Poslovanju)
The subject of this paper is the study of a certain segment of positive environmental law in the Republic of Serbia in the context of administrative legal protection. The leading international instrument in the field of environmental protection is the Convention on Access to Information, Public Participation in Decision-making and Access to Justice in Environmental Matters (Aarhus Convention). The Aarhus Convention rests on the so-called "pillars", the first two of which represent the availability of environmental information and public participation in decision-making. Therefore, the presentation of the administrative and legal protection of the environment in the Republic of Serbia will be presented from the aspect of these two elements, while in the final part of the paper, the application of some of the mentioned institutes will be considered using an example from practice.